2014
DOI: 10.1007/s00466-014-1070-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear frequency response analysis of structural vibrations

Abstract: In this paper we present a method for nonlinear frequency response analysis of mechanical vibrations of 3-dimensional solid structures. For computing nonlinear frequency response to periodic excitations, we employ the wellestablished harmonic balance method. A fundamental aspect for allowing a large-scale application of the method is model order reduction of the discretized equation of motion. Therefore we propose the utilization of a modal projection method enhanced with modal derivatives, providing second-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Thus, various alternative approaches for computation of the matrix Q for the nonlinear case have been suggested. A well‐known method is based on expansion of the eigenmode basis by the so‐called modal derivatives and was successfully applied in several works . However, the approach with modal derivatives has considerable drawbacks.…”
Section: Projection Methods For Model Order Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, various alternative approaches for computation of the matrix Q for the nonlinear case have been suggested. A well‐known method is based on expansion of the eigenmode basis by the so‐called modal derivatives and was successfully applied in several works . However, the approach with modal derivatives has considerable drawbacks.…”
Section: Projection Methods For Model Order Reductionmentioning
confidence: 99%
“…As far as the projection step is concerned, it can be shown that modal reduction and Krylov subspaces are not sufficient for reduction of nonlinear equations . In some scenarios, modal derivatives can be used to enrich the common basis and lead to accurate results for real‐life examples . However, we believe that knowledge of the design space has to be exploited to find appropriate projection for a general nonlinear case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice could be more practical than the nodal fixed frame, as the best choice of the specified fixed nodes in the nodal fixed frame is not straightforward in three dimensional cases. Also, the MDs have been successfully calculated for three dimensional models [29,39] in the inertia frame, to solve nonlinear problems without large rigid body motion. It is worth mentioning that the benefits of the proposed technique will be even more apparent for three dimensional problems that would feature, in general, larger finite element meshes and therefore provide larger gains from the adopted modal approach.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve these singularity issues, many modifications have been suggested, see, eg, previous studies. 1,[18][19][20][21][22][23] However, common to all of the suggestions presented is that they represent some kind of approximation. The approximation issue was, however, solved in Part I of the present work where a set of equations governing the complete MDs were derived by use of perturbation methods.…”
Section: Introductionmentioning
confidence: 99%